A Thiosemicarbazone–Nickel(II) Complex as Efficient Electrocatalyst for Hydrogen Evolution. Issue 12 (22nd November 2016) - Straistari, Tatiana; Fize, Jennifer; Shova, Sergiu; Réglier, Marius; Artero, Vincent; Orio, Maylis
Abstract: We report herein the synthesis and characterization of a new mononuclear nickel complex based on a thiosemicarbazone ligand that exhibits an electrocatalytic behavior for H2 evolution in DMF using trifluoroacetic acid (TFA) as the proton source. Catalysis is observed at quite small overpotential values and a maximum turnover frequency (TOFmax ) of 3080 s −1 was extrapolated for 1 m proton concentration using the foot‐of‐the wave analysis of cyclic voltammetry data. Gas analysis during controlled potential electrolysis experiments confirmed the catalytic nature of the process and production of dihydrogen with 80 % faradaic yield. Quantum chemical calculations indicate that the catalytic mechanism involves first ligand‐based reduction and protonation steps followed by metal‐centered processes. Abstract : Nickel‐centered : A mononuclear nickel complex based on a thiosemicarbazone ligand ranks among the best molecular H2 ‐evolving electrocatalysts in DMF in the catalytic Tafel plot. The catalytic mechanism involves ligand‐based reduction and protonation steps followed by metal‐centered processes.